Nelson-Siegel Model Approach to the Euro Area Yield Curves - Akvilė Mazanauskaitė (Lithuanian Journal of Statistics, 2017)
In this paper Nelson-Siegel model has been examined. The main purpose of this paper is to fit the best Nelson-Siegel model to the Euro Area yield curves and to compare with Lithuanian yields in order to draw conclusions about readiness of Lithuania to join the Euro Area. In order to succeed in achieving the goal, Euro Area zero coupon bonds have been examined and various static Nelson-Siegel models were developed. Also, the mean of absolute errorof the Lithuanian government treasury bills was calculated using the best-fitting Nelson-Siegel model of the Euro Areayields. The results have shown that if the static model is calculated for each year, the yield are described precisely in the model.